Digital transformation as a bridge from 'Leadership-People-Market' to competitive advantage and sustainable growth of logistics service providers in Thailand - Bharis Hongsakul; Chanyaphak Lalaeng; Apinya Ingard (Multidisciplinary Science Journal, 2026)
This study examined the mediating role of digital transformation (DT) in the conversion of organizational potential—entrepreneurial leadership (EL), human capital (HC), and entrepreneurial market orientation (EMO)—into tangible organizational outcomes among logistics service providers in Thailand. The conceptual framework was grounded in the resource-based view (RBV) and dynamic capabilities theory, positing that leadership, people, and market orientation can generate competitive and sustainable advantages only when effectively enabled through digital change. Data were collected from 303 logistics organizations across Thailand via a structured questionnaire, and the relationships among variables were analyzed via partial least squares structural equation modeling (PLS-SEM) via SmartPLS. The results indicate that digital transformation (DT) acts as a fully mediating mechanism linking EL, HC, and EMO to CA and SG. The results provided strong empirical support for all six hypothesized mediation paths, indicating that digital transformation functions as a key mechanism that channels the effects of entrepreneurial leadership, human capital, and entrepreneurial market orientation toward enhancing competitive advantage (CA) and sustainable growth (SG). The overall model demonstrated satisfactory explanatory power and predictive relevance, confirming the robustness and theoretical consistency of the proposed relationships. The findings underscore that the integration of leadership capability, human capital development, and market orientation with digital initiatives contributes significantly to organizational performance in the Thai logistics sector. Consequently, this study not only enriches the theoretical understanding by linking dynamic capabilities with digital transformation but also provides practical guidance for logistics managers to design a digital roadmap that strategically connects “leadership–people–market” with digital processes. This connection fosters both immediate competitiveness and long-term sustainability, serving as a model for digitally driven growth in emerging economies.
Keywords: Educational Leadership and Innovation; Digital Transformation in Industry; Cyberloafing and Workplace Behavior